Standardisasi Karung Plastik Di Indonesia - Indra Putra; kun Harimurti (Jurnal Kimia dan Kemasan, 1978)
Standardization of plastic bag in Indonesia covers Standard of Quality  and Testing Method. Test of plastic bag with Outer Plastic bag + Inner Liner construction is Carried out with "drop test" for filled Plastic bag and with "macro" and "micro test" for empty plastic bag